Outside the box : hand-drawn packaging from around the world - Anderson, Gail, 1962- (2015)
"In an age of slick, computer-generated type and Photoshopped perfection, hand-drawn packing is enjoying a global resurgence. As shorthand for something more authentic, homegrown, handmade, or crafted, hand-drawn packaging is found on everything from supermarket eggs to Chipotle drink cups. In this exhaustive and lavishly illustrated survey, organized by four types--DIY, Art, Craft, and Artisanal--Anderson pulls back the curtain on the working processes and inspirations of forty letterers, illustrators, and designers from all around the world through insightful interviews, process sketches, and her infectious love of the medium"--
Includes bibliographical references (pages 252-253).
Keywords: Packaging -- Design -- Themes, motives; DESIGN / Product